A Novel Three-Dimensional Analysis of Tongue Movement During Water and Saliva Deglutition: A Preliminary Study on Swallowing Patterns - Álvarez, Giannina; Dias, Fernando José; Lezcano, María Florencia; Arias, Alain; Fuentes, Ramón
Deglutition is a complex oral function, and the study of the whole process requires a precise analysis of the elements involved, especially of the tongue biomechanics. We described a three-dimensional analysis of tongue movements during both saliva and water deglutition in participants with normal occlusion. Fourteen participants (25.36 ± 4.85 years) were evaluated, and the movements of anterior, middle, and posterior portions of the tongue were recorded using AG501 3D-electromagnetic articulograph. An average volume (AVS) for water deglutition was determined for each participant. Saliva deglutition was classified according to Bourdiol et al. 35.71% was type I, 14.29% type II, and 50% type III. The greatest displacement on the inferior–superior axis was in the posterior portion, followed by the middle and anterior portions. In the posterior–anterior axis, smallest movement was in the anterior portion. During water deglutition, on the inferior–superior axis, there were statistical differences for 1-AVS between the anterior/middle and anterior/posterior portions of the tongue. There were statistical differences for both ½-AVS and ¼-AVS between the anterior/posterior portions of the tongue. On the posterior–anterior axis, there were no statistical differences among any volume–portion relations. On the medial–lateral axis, there was statistical difference for the ½-AVS between middle and posterior portions. The movement of the tongue portions was influenced by the volume and the element to be swallowed. The amplitude of the movement was directly proportional to the volume of water swallowed.